Effects of Knowledge, Socialization, Services, and Tax Sanctions on the Compliance of Individual Taxpayers Performing Free Work In 2020: A Case Study at a Notary Office in Palembang - Felix Kusuma Fuliyanto (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to investigate the effect of knowledge, socialization, service, and tax sanctions on individual taxpayer compliance at the notary office in Palembang. The data used are primary and secondary data with data collection techniques through literature study, observation, interviews, anddistributing questionnaires to 50 respondents. The data analysis technique used multiple linear regression. Further statistical tests prove knowledge, socialization, and service have a significant effect on tax compliance variables. However, tax sanctions are not proven to have a positive effect on taxcompliance. This research provides benefits to tax agencies to improve taxpayer compliance through knowledge, socialization, and service.